DIVERSIFICATION OF RURAL ECONOMICS IN SABAH: PATTERNS AND DETERMINANTS OF CHANGE - Ubong Imang (Prodi Sosiologi FISIP Universitas Teuku Umar, 2020)
Economic diversification is fundamental in driving economic growth in rural areas. Encouragement of and stimulus for the economic diversification in the rural areas allow for the generation of opportunities and new economic chains. Apart from that it will assist in the diversification of the sources of income for the rural population. In Malaysia, apart from emphasising on development policies, economic diversification began to take place in rural areas through positive developments in the economic sectors other than rural agriculture such as tourism as well as small and medium industries. The importance of leveraging on the opportunities and available space has created a need to examine the pattern and defining factors of economic diversity that is taking place in rural areas. The discussion in this article pays attention to the diversification of the economy that is taking place in the rural areas in Sabah by selecting the village of Tambatuon as a study area. In addition to the secondary data, the data is also obtained through observations, involvement in the newly created economic activities and interviews with the village heads and members of the Village Community Management Council (MPKK). The results of the study confirm that economic diversification in rural areas is in place. Most of the new economic activities exist based on the initiative of the villagers who receive support from the Government and non-governmental organisations. Nevertheless, the study also shows that the ongoing economic diversification process is still limited to the horizontal level. Hence, there is considerable potential for economic diversification that can be further expanded to enhance the competitiveness of the rural population in general. In this context, rural residents should be creative by using available local resources from the surroundings to broaden the process of economic diversification. Assistance and external support, especially from the Government, is significant in providing an environment that can stimulate economic growth to ensure that the process of diversifying the economy continues to flourish and becomes sustainable.